Analysis of the JAKLITERA Website Information System Using the PIECES Method to Enhance Library Services at the Library and Archives Office of DKI Jakarta Province - Anandita Putri, Syaharani; Tanti Rahayu, Agus; Aditiya, Arya (Yayasan Kawanad, 2025)
The advancement of information technology has shifted libraries from traditional physical services to digital platforms. One example is JAKLITERA, a web-based information system developed by the Provincial Library and Archives Office of DKI Jakarta. This study aims to evaluate the performance and service quality of JAKLITERA using the PIECES framework (Performance, Information, Economics, Control, Efficiency, Service). A mixed approach was applied, combining quantitative data from 100 user questionnaires with qualitative insights from observation and administrator interviews. Validity and reliability testing confirmed that all research instruments were appropriate for analysis. Results showed that the Economics dimension achieved the highest mean score (3.95), while Control received the lowest (3.39). Overall, the average score of 3.62 categorized JAKLITERA as “satisfactory,” yet highlighted the need for improvements in security mechanisms and clarity of information. These findings suggest that JAKLITERA functions effectively as a digital literacy platform but requires continuous evaluation, technical optimization, and user-centered enhancements to ensure sustainable service delivery.